Harmonisation and unification and their influence on the evolution of national legal systems - Ponomareva, Darya S. (Journal of the Belarusian State University. International Relations, 2022)
The author of the article explores the concepts of harmonisation and unification. Both are used in legal texts and doctrinal sources, but the distinctions among them and the implications for the evolution of the national legal systems are still poorly understood. The aim of the research is to clarify the similarities and differences between these and related concepts and understand how the processes to which they refer influence legal change. It is concluded that harmonisation and unification are uneven and fragmentary processes, even though they are often equated. National legal systems retain substantial differences and specificities precluding the assimilation of many legal norms from other jurisdictions and creating formidable barriers to harmonisation. We also find that shared history, legal traditions and commonalities in the legal order and elements of legislation facilitate harmonisation, and international organisations lay the groundwork for harmonisation. We present examples of successes in the unification of material and procedural law and highlight the essential role of supranational bodies such as the Court of Justice of the European Union and the Court of the Eurasian Economic Union in the uniform application and interpretation of the common rules.